Arm movement strategies did not influence emotional state and static postural control during height-induced postural threat in children and young adults - Wissmann, Anna M.; Hill, Mathew W.; Muehlbauer, Thomas; Lambrich, Johanna (Frontiers in Human Neuroscience, 2025)
BackgroundEmpirical evidence in adults suggests that height-induced postural threat led to an increased reliance on an ankle control strategy (i.e., postural “stiffening” response). However, little is known whether children (i.e., due to ongoing maturation) show a similar pattern and how this is affected by the used arm movement strategy.ObjectiveThe objective of this study was to compare the effects of different arm movement strategies on subjective and objective indicators related to standing at or above ground-level in children versus young adults.MethodsTwenty-six children (age: 9.8 ± 0.6 years) and 23 young adults (age: 24.7 ± 4.0 years) performed the tandem stance whilst standing at both ground-level (no threat) and 80 cm above ground (threat). During both, participants performed the task with free and restricted arm movements. Self-reported emotional state outcomes (i.e., balance confidence, fear of falling, perceived instability, conscious balance processing) were assessed and used as subjective indicators. Static balance outcomes (i.e., postural sway amplitude, frequency, and velocity) were measured and used as objective markers.ResultsIrrespective of arm movement condition, children showed an increase in fear of falling and young adults a decrease in postural sway frequency when standing above ground than on ground level.ConclusionThe findings indicate that children are emotionally reactive but possibly not able to translate that into meaningful motor adaptation. Conversely, young adults react motorically but do not necessarily transfer that into an emotional response.